2016
DOI: 10.1021/acs.nanolett.6b02547
|View full text |Cite
|
Sign up to set email alerts
|

Long-Circulating Au-TiO2 Nanocomposite as a Sonosensitizer for ROS-Mediated Eradication of Cancer

Abstract: Although sonodynamic therapy (SDT) has emerged as a potential alternative to conventional photodynamic therapy, the low quantum yield of the sonosensitizer such as TiO nanoparticles (NPs) is still a major concern. Here, we have developed hydrophilized Au-TiO nanocomposites (HAu-TiO NCs) as sonosensitizers for improved SDT. The physicochemical properties of HAu-TiO NCs were thoroughly studied and compared with their counterparts without gold deposition. Upon exposure of HAu-TiO NCs to ultrasound, a large quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
269
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(283 citation statements)
references
References 42 publications
0
269
0
7
Order By: Relevance
“…Compared to bare TiO 2 NPs, the authors showed that Au-TiO 2 NPs generated a greater amount of ROS and lead to complete suppression of tumor growth, in-vivo (Fig. 6) [135]. More recently, Dai et al [136] developed a novel nanoconstruct (NC) functionalizing two-dimensional (2D) reduced graphene oxide (GR) with TiO 2 NPs (TiO 2 -GR NC).…”
Section: Cytotoxic Effects Arising From Nanoparticle-activation By Camentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to bare TiO 2 NPs, the authors showed that Au-TiO 2 NPs generated a greater amount of ROS and lead to complete suppression of tumor growth, in-vivo (Fig. 6) [135]. More recently, Dai et al [136] developed a novel nanoconstruct (NC) functionalizing two-dimensional (2D) reduced graphene oxide (GR) with TiO 2 NPs (TiO 2 -GR NC).…”
Section: Cytotoxic Effects Arising From Nanoparticle-activation By Camentioning
confidence: 99%
“…Hydrophilized Au-TiO 2 NPs (HAu-TiO 2 NCs) resulted in tumor regression. Adapted with permission from [135]. Copyright 2016, American Chemical Society.…”
Section: The Cytotoxic Effects Of Sonodynamic Therapymentioning
confidence: 99%
“…Usually, inorganic particles have high physical and chemical stability . TiO 2 , as the most typical representative, can enhance SDT for cancer treatment without connecting any organic material, but the rapid combination of electron–hole pairs limits the generation of ROS, then limits the efficiency of SDT . Organic sound sensitizers, accounting for the majority in sonosensitizers, are mainly composed of porphyrins and their derivatives with excellent properties of producing ROS under the stimulation of external energy .…”
Section: Tumor Therapymentioning
confidence: 99%
“…[343][344][345][346] Chen's team has been aggressively explored synergistic SDT for cancer therapeutics based on nanomedicine. SDT has the advantages in deeper tissue penetration and nonphototoxicity to NT compared with PDT, providing a promising cancer therapy paradigm and receiving an increasing amount of research attention.…”
Section: Other Synergistic Surgerymentioning
confidence: 99%